Mechanisms of the effect of gut microbes on depression through the microbiota-gut-brain axis - Zhou, Xiangyan; Wang, Sixing; Wang, Xiaohui; Chen, Xinran; Zhou, Pei; Ma, Kai; Zhang, Peng (Frontiers in Nutrition, 2025)
Depression is a significant public health issue which exerts profound psychological and social impacts on both individuals and society. However, existing therapeutic strategies often exhibit limited efficacy. Accumulating evidence underscores the vital role of gut microbiota in the pathophysiology of depression through the microbiota-gut-brain (MGB) axis. This involves multiple mechanisms, including short-chain fatty acid (SCFA) metabolism, communication via the vagal nerve, regulation of the hypothalamic-pituitary-adrenal (HPA) axis, and immune-inflammatory interactions. This review provides a comprehensive review of the mechanisms through which gut microbiota influences depression via the MGB axis. It synthesizes recent achievements in this field and evaluates the potential of microbiome-targeted therapies for depression treatment. Furthermore, it outlines future research directions to establish a theoretical framework for novel therapeutic approaches and to foster the development of this area.